HUBUNGAN ANTARA SELF AWARENESS DENGAN KADAR GLUKOSA DARAH PADA PASIEN DM TIPE 2 (Studi di Poli Penyakit Dalam RSUD Jombang) - Kasana, Rizki Uswatun; Auliasari Siskaningrum, Hindyah Ike (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2019)
Poor self-management can make a serious complications in DM patients. One of the indicators of poor self-management is uncontrolled blood sugar levels. Uncontrolled blood sugar levels caused by self awareness of patients to chronic disease treatment regimens are generally low not least in DM patients. The purpose of this study is to know the relationship between self awareness with blood glucose levels in patients with type 2 diabetes In Poly Disease In RSUD Jombang. The design of this study is correlational analysis with cross sectional method. The Population of Diabetes Mellitus type 2 in Poli In RSUD Jombang a total of 535 people. The Sampling technique using purposive sampling with a sample of 134 people. The research instrument used observation sheet with data processing editing, coding, scoring, tabulating and statistical test using spearman rank test. Most of the research (65,7%) of self-awareness respondents were less than 88 people, most of them (66,4%) of blood sugar was high 89 people. Spearman rank test shows that the significance value r = 0,000 <a (0,05), so H0 is rejected. This study can be concluded that the relationship between self awareness with blood glucose levels in patients with type 2 diabetes In Poly Disease In RSUD Jombang. Keywords: DM, blood glucose level, self awareness